Systematic Postsynthetic Modification of Nanoporous Organic Frameworks for Enhanced CO2 Capture from Flue Gas and Landfill Gas - Islamoglu, Timur (2016)
Controlled postsynthetic nitration of NPOF-1, a nanoporous organic framework constructed by nickel(0)-catalyzed Yamamoto coupling of 1,3,5-tris(4-bromophenyl)benzene, has been performed and is proven to be a promising route to introduce nitro groups and to convert mesopores to micropores without compromising surface area. Reduction of the nitro groups yields aniline-like amine-functionalized NPOF-1-NH2 that has a micropore volume of 0.48 cm3 g–1, which corresponds to 71% of the total pore volume and a Brunauer–Emmett–Teller surface area of 1535 m2 g–1. Adequate basicity of the amine functionalities leads to modest isosteric heats of adsorption for CO2, which allow for high regenerability. The unique combination of high surface area, microporous structure, and amine-functionalized pore walls enables NPOF-1-NH2 to have remarkable CO2 working capacity values for removal from landfill gas and flue gas. The performance of NPOF-1-NH2 in CO2 removal ranks among the best by porous organic materials.